Spare parts : the true story of four undocumented teenagers, one ugly robot, and an impossible dream - Davis, Joshua, 1974-; Grande, Reyna (Farrar Straus Giroux Books for Young Readers, an imprint of Macmillan Publishing Group, LLC, 2023)
"The young readers' edition of the bestselling adult book of the same name"--